Strategi Kepala Sekolah dalam Meningkatkan Mutu Guru Berbasis Perbaikan Berkelanjutan di SDN 008 Samarinda Ulu - Kumullah, Rahima (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This research examines the principal's strategy in improving teacher quality through continuous improvement at SDN 008 Samarinda Ulu. Using a qualitative approach, data was collected through observation, interviews and documentation. The research results show that strategies such as classroom observation, teacher supervision, professional training, and collaborative learning communities play an important role in encouraging teacher development. Challenges include resistance to change, limited technology skills, and workload pressures. Nevertheless, innovative programs such as Si MANTAP are quite promising in improving teaching competence and collaboration. This study underscores the importance of sustainable strategies to address the growing educational demands of society 4.0 and 5.0.